Unsteady flow analysis regarding stall flow and rotating cavitation in the first-stage of a multistage LNG cryogenic submerged pump. (January 2023) - Wang, Cong; Guo, Lin; Liu, Zhigang; Zhang, Yongxue; Li, Zhuoliang
Abstract: In this paper, the evolution of vortex structure and energy conversion process under the coupling of stall and cavitation flow (CSC) in the first-stage of a multistage LNG cryogenic submerged pump are numerically studied in detail, using a time-scale-driven hybrid URANS/LES turbulence model and a mushy interfacial dynamics cavitation model. The flow instability diagnostic parameter, PVS, is then established combining the first and second laws of thermodynamics. Further, the dynamic behaviors under CSC are analyzed by Liutex method and the fluctuations of vortex intensity are investigated in time-frequency domain. Results show that compared with the oscillation process of the pump head, PVS is more intuitive to depict the stall state. It is treated as light and deep stall as PVS drops to 0.2 and 0.15, while PVS is further reduced and finally locks at about 0.12. For the above conditions, vortices at the inlet section involves high-frequency cavity-shedding vortex and low-frequency impact vortex. The middle separation region absorbs the upstream shedding vortex and transports the separation vortex downstream, whereas vortices with the highest intensity locates at the outlet diffusion section in the helical shape. Among the vortex-vortex interaction, broadband oscillations get more significant under CSC.